Rhythmic Vitality: A Study of the Artistic Expressions of Chinese Animation Master Te Wei - Dong, Jun; Liu, Lihui (International Journal of Culture and History, 2023)
The author intends to do a comprehensive analysis and examination of Mr. Te Wei’s notable animation works, including "Tadpole Looking for Mother," "Pastoral Flute," "Landscape," "Proud General," and several more. To commence, this analysis will begin by examining the works of Mr. Te Wei and their significance as a foundation for understanding. Subsequently, the locations within Mr. Te Wei’s works that hold educational value will be scrutinised, leading to the formulation of the research’s objective. This text elucidates the comprehensive process of Mr. Te Wei’s creative cognition, effectively conveying a denouement that is both comical and dramatic. In contemporary culture, the intensification of labour and the pace of life have contributed to an increasing burden on individuals. Notably, a considerable number of Chinese animations have excessively emulated Japanese animations, therefore neglecting the distinctive cultural attributes of our own nation. Hence, this article endeavours to systematically expound upon the artistic style and expressive techniques of Mr. Te Wei, a renowned figure in Chinese animation, by analysing representative works such as "Shepherd’s Flute" and "Landscape". The aim is to cultivate the audience’s appreciation for Mr. Te Wei’s creations and enhance their comprehension of his artistic expression. The artistic expression exhibited by Mr. Te Wei, a prominent figure in Chinese animation, has the potential to evoke inspiration and contemplation among viewers. Specifically, his work prompts reflection on the dearth of humour within contemporary society and the absence of national cultural elements in the realm of animation.